METODE BAYESIAN PADA SISTEM ANTREAN PELAYANAN MENGGUNAKAN GUI R (Studi Kasus: Antrean Pelayanan di Kantor Dinas Kependudukan dan Pencatatan Sipil Kota Semarang) - Atikah Mufidah; Sugito Sugito; Di Asih I Maruddani (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2022)
The increase population of Semarang City has given many kinds of problem from births, deaths, marriages and other important events. The change of population identity data causes the number of visitors to the Semarang City Dispendukcapil to increase so that the service system becomes busy. The study aims to determine whether the service system in the Dispendukcapil is good or not. This can be known by determining the distribution of arrival patterns and service patterns to obtain a queuing system model and system performance measures. In this study, the distribution of arrival patterns and service patterns is determined by finding the posterior distribution using the Bayesian method. The Bayesian method was chosen because it is able to combine the distribution of the sample in the current study with previous information for the same case. Posterior distribution can be obtained if it has elements, namely prior distribution and likelihood function. The distribution of arrival patterns and service patterns obtained from prior information, follows the Discrete Uniform and Log-Normal distribution. Based on the calculation and analysis of the posterior distribution, the service system model of the Dispendukcapil Semarang City is obtained, namely for the Customer Service counter, and for the legalization counter and the population document service counter with a good service system.Keywords:Population, Dispendukcapil Semarang City, queue, Bayesian, prior distribution, posterior distribution, queuing system model, Beta, Gamma, Inverse Gamma.